2009
DOI: 10.1143/jjap.48.061403
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Properties of BaZrO3 Doped Sr0.8Bi2.2Ta2O9 Thin Films

Abstract: Novel sol–gel derived Sr0.8Bi2.2Ta2O9 (SBT) doped with 5 and 7% molar ratio BaZrO3 (BZ) thin films were fabricated, characterized, and electrical properties were evaluated with Pt electrodes. X-ray diffraction (XRD) analysis showed all the characteristic peaks of the layered perovskite structure with (115) orientation and slight peak broadening by BZ doping. X-ray photoelectron spectra (XPS) showed a small shift in the Sr 3d peak with BZ substitution. Scanning electron microscopy (SEM) cross-sectional photogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Furthermore, it is also attributed to electron trapping/detrapping. Further discussion about the leakage current was previously reported in [13][14][15].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, it is also attributed to electron trapping/detrapping. Further discussion about the leakage current was previously reported in [13][14][15].…”
Section: Resultsmentioning
confidence: 84%
“…It is noted that, for higher doping, (115) peak becomes slightly broader and less intense. This is due to a degradation of crystallinity which affects ferroelectricity by means of both lowering remanent polarization and dielectric constant [13][14][15]. Surface microstructure of SBT examined by SEM [15] showed that a dense structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of Sr 3d spin-orbit-split pairs constitutes two overlapping peaks. While the pairs of lower binding energy are associated with Sr ions in the perovskite structure, those of higher binding energy are assigned to Sr in oxide or carbonate [20]. Broadening of Sr 3d 3/2 and 3d 5/2 evidenced Sr ions in the perovskite structure by Ba substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, enhancement of defect concentrations causes a decrease in remanent polarization. Hence, such mobile charges have ability to affect ferroelectric and electrical properties seriously [20]. The impact of co-substitution on ferroelectric properties was studied by measuring polarization vs. switchable component of polarization were decreased by increasing the substitution ratio.…”
Section: Resultsmentioning
confidence: 99%